2009
DOI: 10.1148/radiol.2521081059
|View full text |Cite
|
Sign up to set email alerts
|

Does Arterial Spin-labeling MR Imaging–measured Tumor Perfusion Correlate with Renal Cell Cancer Response to Antiangiogenic Therapy in a Mouse Model?

Abstract: Purpose:To determine whether arterial spin-labeling (ASL) magnetic resonance (MR) imaging findings at baseline and early during antiangiogenic therapy can predict later resistance to therapy. Materials and Methods:Protocol was approved by an institutional animal care and use committee. Caki-1, A498, and 786-0 human renal cell carcinoma (RCC) xenografts were implanted in 39 nude mice. Animals received 80 mg sorafenib per kilogram of body weight once daily once tumors measured 12 mm. ASL imaging was performed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
88
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 53 publications
(25 reference statements)
6
88
1
1
Order By: Relevance
“…Although principally employed for cerebral blood flow quantification, ASL has begun to see applications outside of the brain, with the kidney being one of the first and most popular sites. Several studies have demonstrated the feasibility of ASL quantification of renal perfusion in both healthy and disease states (12)(13)(14)(15)(16). However, a number of quantification issues remain to be addressed, such as: how perfusion estimates may be confounded by different flow characteristics, the positioning and orientation of the tagging slab, and tissue and arterial transit times.…”
mentioning
confidence: 99%
“…Although principally employed for cerebral blood flow quantification, ASL has begun to see applications outside of the brain, with the kidney being one of the first and most popular sites. Several studies have demonstrated the feasibility of ASL quantification of renal perfusion in both healthy and disease states (12)(13)(14)(15)(16). However, a number of quantification issues remain to be addressed, such as: how perfusion estimates may be confounded by different flow characteristics, the positioning and orientation of the tagging slab, and tissue and arterial transit times.…”
mentioning
confidence: 99%
“…These findings correlated with the lack of response of Caki-1 tumors to sorafenib therapy, possibly suggesting that low levels of perfusion on ASL may be a useful biomarker for predicting poor responsiveness to certain types of antiangiogenic therapy. 75 Although blood flow changes on ASL after antiangiogenic therapy varied in these animal models, its regional distribution within the tumors corresponded tightly to their histopathologic appearance. Regions with high signal intensity on ASL correlated to viable tumor, with zones of absent or diminished signal (ie, <2 mL/100 mg/minute) representing necrosis.…”
Section: Asl Mrimentioning
confidence: 79%
“…Caki-1 (sorafenib resistant), A498 (sorafenib sensitive), and 786-0 (early response followed by rapid development of resistance by Day 5) tumors exhibited different levels of blood flow on ASL MRI at baseline. 75 Specifically, Caki-1 tumors demonstrated minimal blood flow at baseline (10.2 mL AE 9.0 mL/100 mg/minute) relative to 786-0 tumors (75.1 mL AE 28.6 mL/100 mg/minute) and A498 tumors (80.1 mL AE 23.3 mL/100 mg/minute). These findings correlated with the lack of response of Caki-1 tumors to sorafenib therapy, possibly suggesting that low levels of perfusion on ASL may be a useful biomarker for predicting poor responsiveness to certain types of antiangiogenic therapy.…”
Section: Asl Mrimentioning
confidence: 92%
See 2 more Smart Citations